Mechanism of Solar Activity Triggering Earthquakes and Volcanoes: Consequence of Whole-Earth Decompression Dynamics - Herndon, J. Marvin (European Journal of Applied Sciences, 2022)
Recently published scientific evidence implies that activities on the sun cause earthquakes and volcanic eruptions on Earth. However, the geophysical basis is inexplicable within the currently popular, but flawed geoscience paradigms. However, the mechanism of solar activity provoking earthquakes and volcanic eruptions follows logically from Whole-Earth Decompression Dynamics. Here I disclose the mechanism for changes in solar weather triggering earthquakes and volcanoes which operates as a multi-stage amplifier: A change in the charged particle flux impinging the Earth’s magnetic field induces electric current into the georeactor, which causes ohmic heating, which disrupts sub-shell convection, which results in extra uranium settling-out, which causes a burst of nuclear fission energy, which replaces some of the lost heat of protoplanetary compression, which causes a burst in whole-Earth decompression, which results in a burst of heat emplaced at the base of the crust and/or Earth’s surface experiencing a bit of decompression-driven movement, the extent of which is a function of the degree of sub-shell convection disruption.